Pengaruh Harga Dan Kualitas Produk Lipcream Wardah Terhadap Keputusan Pembelian Pada Toko Dandan Depok - Erika Yolanda; Irwan Raharja (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
The development of the cosmetic industry is increasing so that companies must innovate and must provide appropriate prices and maintain the quality of their products. Price is indeed the first measuring factor that is assessed by consumers as well as for the quality of the product. This study aims to determine the Price and Quality of Lipcream Wardah Products on Purchasing Decisions partially and simultaneously. The object of this study is Wardah Lipcream Products. In this study, primary data was collected by 100 respondents buying and using Wardah Lipcream products. The sampling method in this study was non-probability sampling with accidental sampling technique. The test phase was carried out with the results of the Validity and Reliability tests stating Valid and reliable, and normality test results 0.200 , multicollinearity test tolerance values 0.700 and VIF 1.429 and heteroscedasticity test spread randomly, autocorrelation test, multiple linear analysis, t test, f test and test coefficient of determination. This study used a questionnaire instrument with the help of Google Form and valid data which was collected by 100 respondents. This test used the SPSS Version 24 tool.The results of this study indicate that the variable price and product quality have a positive effect on purchasing decisions.